The prejudices of teacher candidates pertaining to management - Demirtas, Zuelfue (Elsevier Science Bv, 2009)
The aim of this research was to determine teacher candidates' prejudices pertaining to management. For this aim, in 2007-2008 academic year, the thoughts of students, who are in the fourth grade of Firat University's Education Faculty and students who are taking their non-thesis master degree in Firat University, are taken into consideration. To gather data, a prejudice survey that includes four factors is used. According to data we have reached, teacher candidates agree with the items in ''Situational Management'' and ' 'Charismatic Management '' factors at a average level and they don't agree the items in X Theory and the Absence of Management's schooll '' and '' Uselessness of Personnel '' factors. Students, taking their non-thesis master degree have more prejudice than Education Faculty's fourth grade students. (C) 2009 Elsevier Ltd. All rights reserved
World Conference on Educational Sciences -- FEB 04-07, 2009 -- Nicosia, CYPRUS
Keywords: Management; educational management; teacher candidate; prejudice